Increasing capital market literacy for MSMEs in business development in Palembang City - Hidayat, Ariodillah; Liliana, Liliana; Andaiyani, Sri; Gustriani, Gustriani; Shodrokova, Xenaneira (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to improve financial literacy and increase capital market understanding in 33 Micro, Small and Medium Enterprises (MSMEs) in Ilir Barat II Palembang City. The initiative, which was carried out in collaboration with the local government and the Faculty of Economics, Sriwijaya University, focused on providing literacy and training in financial markets. The goal is to equip MSME entrepreneurs with important skills for business development. The initiative addresses challenges such as limited financial knowledge and reliance on bank loans. Utilizing a collaborative approach, the program includes lectures, discussions, and evaluations. The results showed a positive response from participants, with increased awareness and interest in participating in the capital market. The significance of the location as a Palembang Songket Handicraft center and liaison shows the relevance of the program. The success of this initiative has positive implications for MSMEs, encourages a better understanding of capital markets, and fosters potential participation in the Initial Public Offering (IPO) process. Overall, community service programs contribute to improving economic literacy and opening opportunities for MSMEs to find alternative sources of funding for business development.